From practice to theory, Ovide Decroly for Brazilian classrooms: a tale of appropriation. Issue 6 (1st November 2016) - Arce Hai, Alessandra; Simon, Frank; Depaepe, Marc
Abstract: In this article the authors attempt to understand and apprehend the dynamic transnational movement of the appropriation of Ovide Decroly's ideas and its 'flight to Brazilian lands'. They work with the assumption that Decroly's ideas, entangled in different levels, are articulating and interacting with the Brazilian cultural and educational environment. The intention is to get close to the classroom and to have a glimpse at the practices inside. To approach classroom practices, a traditional archive has been chosen, which is constituted by the pedagogical press, to have a thorough look within: pedagogical periodicals and pedagogical collections, and analyses of two books and six articles concerning Decroly's ideas published in Brazil between 1927 and 1931. Methodological discussions are first introduced, and the substantial contents of the books and articles concerning Decroly's ideas under study are then presented. In the analyses the authors debate what happened to Decroly's ideas when Brazilian teachers and intellectuals used them.